PRAGMATIC FEATURES OF POETIC TEXTS (Academia Science Repository, 2023)
In this article, the artistic features of the syntactic-semantic-pragmatic relations of the content created through the relation of the components of the poetic text are described. Every word, phrase, expression, and sound in a poetic work is a means of expressing the poet's feelings, thoughts, and mood, as a form, it affects the reader, means of expression of a poetic work, the color of the image, the harmony of form and content. the expressive possibilities of the words and other linguistic tools used in it are analyzed.